Livro-reportagem mães na dor: mulheres órfãs de filhos - Oliveira, Bruna Vieira de (2017)
This work is the result of a construction of a nonfiction book of five mother?s profile of Grupo Mães na Dor (Mothers in sorrow group), located in João Pessoa city. It tells the stories of these women who had their children dead in a tragic way, victims of murders. Some murderers have been judged, but other ones remain unpunished. The presented journalistic production is a requirement for the completion of the course of the Programme of Postgraduate in Journalism of Federal University of Paraiba, which allows the elaboration of a media product, and also a dissertation in a traditional/conventional standard. Thence, this product approaches aspects related to the violence in Paraiba context, through the point of view and register of distress of these women who joined together to deal with the pain, mourning, and the struggle for justice. The escalation of violence must be presented by the media not only in a factual way, but in an analytic way, investigating and humanised, providing reflexions and debates that lead to actions of social changes in this context. Thus, this work aims to narrate the stories of life of the characters, revealing their efforts for overcoming the pain and present who the victims of the tragedies were. A great review of literature was made through the following authors: Lima (2009), Belo (2013), Vilas Boas (2003), Pena (2015), Da Matta (1978), Medina (2008), Benjamin (1987), Piccinin (2012), Fortes (2014), Sóster (2012) e Morin (1973), et al. The research and construction of this nonfiction book occurred between March of 2015 and July of 2017. The violence must be comprehended in its social origins, in an individual level, its causes and effects. The role of journalism is not only inform, but also debate such points. Technique of researches supported in sociology and anthropology were used in the preparation of this work, such as the stories of life, memories, and participant observation. These supports assist in sensitive and deeper comprehension of the report. When well aplied, the techniques aggregate quality to the journalistic information. Concepts of authors, such as Geertz (2008), Bosi (1994) and Queiroz (1988), were used. It is possible to conclude that among the interviewees there is a general discontentment with the Justice, leading with the pain and the continual desire to perpetuate the memory of their children. For those mothers, the criminal conviction is more than punishment; it serves as example to inhibit other murders and avoiding more women being part of this group. The union is the main tool for the activities, for the mutual comfort and activism. The informal language prevails in this narration to show more authenticity to the report. Narration, description, dialogs, direct and indirect speech, change in the narrative focus (first and third person), are mixed according to the power that the testimonies require to be reported. The texts begin with a speech of the character in first person, about the hardest event in the past, present or future .Some dialogs less relevant were maintained due to revealing interesting nuances. The interviews are the main point of this work, which occurred, most of them, in those families? houses, in their comfort ambient.